The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5902/1980509827732
|View full text |Cite
|
Sign up to set email alerts
|

CRESCIMENTO E QUALIDADE DE MUDAS DE Cassia <i>grandis Linnaeus</i> f. EM RESPOSTA À ADUBAÇÃO FOSFATADA E CALAGEM

Abstract: RESUMOO objetivo deste estudo foi avaliar o crescimento e a qualidade de mudas de Cassia grandis Linnaeus f. (cássia-rosa) em função da adubação fosfatada e da calagem. Os tratamentos foram representados por um fatorial de seis níveis de fósforo (0, 120, 240, 360, 480 e 600 mg dm -3 ) por cinco níveis de saturação por bases do substrato (3,5 (original), 25, 40, 55, 70%), sendo dispostos no delineamento em blocos ao acaso, com quatro repetições. Aos 65 dias após a repicagem, foram medidos a altura da parte aére… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
25

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 13 publications
1
21
0
25
Order By: Relevance
“…A phosphorus efficiency was also observed by other researchers. Freitas et al (2013) reported a positive DQI effect in the dose of 143.16 mg seedling -1 of P in sugar-apple seedlings, and Freitas et al (2017) reported an ascending linear effect for the DQI, in which the greatest phosphorus dose of 600 mg dm -3 Figure 1. Stem diameter (a), proportionally to the use of triple superphosphate (TSP) and irrigation water electrical conductivity (iwEC) levels; plant height (b); shoot dry mass (c); total dry mass (d); absolute growth rate (e); relative growth rate (f); and the Dickson quality index (g), proportionally to the use of TSP in sugar-apple seedlings.…”
Section: Resultsmentioning
confidence: 97%
“…A phosphorus efficiency was also observed by other researchers. Freitas et al (2013) reported a positive DQI effect in the dose of 143.16 mg seedling -1 of P in sugar-apple seedlings, and Freitas et al (2017) reported an ascending linear effect for the DQI, in which the greatest phosphorus dose of 600 mg dm -3 Figure 1. Stem diameter (a), proportionally to the use of triple superphosphate (TSP) and irrigation water electrical conductivity (iwEC) levels; plant height (b); shoot dry mass (c); total dry mass (d); absolute growth rate (e); relative growth rate (f); and the Dickson quality index (g), proportionally to the use of TSP in sugar-apple seedlings.…”
Section: Resultsmentioning
confidence: 97%
“…According to Freitas et al (2017) and Delarmelina et al (2013), greater estimates of RDW mean better seedlings performance after planting, since the root system will be able to better anchor the seedling, allow better water and minerals absorption, and easly translocate water and minerals to stem. Thus, seedlings with lesser RDW estimates may reduce plants growth speed and increase costs for plantations maintainance over time (BEHLING et al, 2014;LOPES et al, 2016;FREITAS et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Freitas et al (2017) described the same, considering that various parameters allow nursery manegers to better choose seedlings that will perform better after planting. Tsukamoto-Filho et al (2013) and Lopes et al (2014) also refer to the management practices needed for plantations maintenance and related costs.…”
Section: Resultsmentioning
confidence: 99%
“…Corroborating with the other growth variables, the dose of 3 g of NPK under these conditions decreased 38.86% the quality of the seedlings as the doses of manure increased, probably due to this dosage of the mineral fertilizer causing phytotoxicity. Considering the exposed, it is assumed that the best combination for production of cashew tree seedlings was obtained using the dose of 1 g of NPK conciled with 200 g of bovine manure, because, as affirm Freitas et al (2017) the higher the quality index of the more standardized seedlings these are. The reduction will be observed in the quality of seedlings from 300 g manure and NPK 3 g dose is due to the excess salts from both the manure as fertilizer, these respective concentrations, similar results were found by Oliveira et al (2015) when studying guava rootstocks under different sources and proportions of organic materials, which observed higher quality of seedlings in the proportion of 40% of the organic material declining with increasing proportion.…”
Section: Resultsmentioning
confidence: 99%